Elemental analysis in the scales of commercially important coastal fishes and their connections with fish feeding habits and habitats - Parvez, Md. Sohel; Hoque, Md. Imdadul; Siddique, Md. Nurul Momen; Rahman, Mohammad Mizanur; Baranyai, Edina; Sajtos, Zsófi; Döncző, Boglárka; Aib, Haithem; Kader, Md. Abdul; Simon, Edina; Czédli, Herta (Frontiers in Marine Science, 2025)
Fish scales absorb different elements into the calcified matrix from surrounding waters as well as from the foods consumed. Scales microchemistry is drawing rising attention for its applicability in a wide range of fields, including environmental and ecological studies. The article represents an elemental analysis of the scales of five commercially important coastal fishes: Tenualosa ilisha, Sillaginopsis panijus, Lates calcarifer, Otolithoides pama, and Rhinomugil corsula. The concentrations of different essential and trace elements were measured using inductively coupled plasma optical emission spectrometry (ICP-OES), and their distribution on scales was mapped using micro-X-ray fluorescence (μ-XRF). The detected elements were categorized into five groups based on their overall mean concentrations: the most, considerable, moderate, low, and least available. The concentration (mg kg−1) of Ca was the highest (107472.32-181002.76) followed by P (41572.43-79042.02) among the elements in the studied fish scales, independent of species. The hierarchy of the overall mean concentration of elements was Ca>P>S>Mg>Na>K>Sr>Zn>Fe>Al>Ba>Mn>Cu>Cr. Element concentrations varied across fish feeding habits and habitats. Carnivore fish were found to have higher concentrations of K, Sr, and lower Fe than that in planktivore fish. The concentrations of Cr, Fe, S, Sr, and Zn were higher in demersal fish’s scales, whereas pelagic fish were found to have higher levels of Al, Ba, Ca, Cu, K, Mg, Mn, Na, and P. Element: Ca ratios, especially Sr: Ca, Mn: Ca, and Ba: Ca ratios, have potential implications as habitat signatures. Typically, fish otoliths are used for environmental and ecological purposes that involve cutting and sacrificing the sample. Employing scales instead could be a non-lethal alternative, crucial for sustainable fisheries management, especially for rare, vulnerable, or migratory fish.